2021
DOI: 10.1021/acsomega.1c00369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Benzhydrylpiperazine-Coupled Nitrobenzenesulfonamide Hybrids

Abstract: A series of novel benzhydryl piperazine-coupled nitrobenzenesulfonamide hybrids were synthesized with good to excellent yields. They were tested for in vitro inhibition of mycobacterial activity against the Mycobacterium tuberculosis H37Rv strain, in vitro cytotoxicity MTT (RAW 264.7cells) assay, nutrient starvation (H37Rv strain), and ability to block Cav3.2 T-type calcium channels. Novel hybrids did not inhibit T-type calcium channels, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…34 The cytotoxicity profile of anti -TB drugs isoniazid and rifampicin was also screened for comparison purpose (Table 1). 35 The SI values for 5d , 5e , and 5h are >30, indicating low cytotoxicity with high selectivity and additional suitability in order to generate potential lead antitubercular agents for further development.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…34 The cytotoxicity profile of anti -TB drugs isoniazid and rifampicin was also screened for comparison purpose (Table 1). 35 The SI values for 5d , 5e , and 5h are >30, indicating low cytotoxicity with high selectivity and additional suitability in order to generate potential lead antitubercular agents for further development.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Vijayakumar et al have designed the novel benzhydryl piperazine-coupled nitrobenzenesulfonamide hybrids (11)(12)(13)(14)(15)(16)(17)(18) via molecular hybridization of benzhydrylpiperazine, amino acids, and nitrobenzenesulfonamide and revealed total eight derivatives with MICs of 0.78 μg/mL (Figure 6). [42] The MICs of these compounds were compared with isoniazid (0.05 μg/mL), ethambutol (1.56 μg/mL) and comparable with rifampicin (0.10 μg/mL). Further, 2,4-dinitro groups on benzene ring found to increase anti-TB activity rather than 2-or 4-nitro substitutions.…”
Section: Piperazinementioning
confidence: 99%
“…Indeed, sulphonamide analogues are known to exhibit a wide range of pharmacological activities particularly responsible for the enhanced anti-TB activity 12 , 13 . Moreover, our recent finding reveals that dinitro-substituted benzene derivatives have superior in vitro anti-TB activity 6 compared with monosubstituted benzene derivatives probably due to electron-deficient aromaticity 14 .…”
Section: Introductionmentioning
confidence: 98%
“…Benzofuran is a class of fused heterocyclic compound having oxygen with a large spectrum of biological activities 3 , 4 with relatively few examples of anti TB activity. The literature survey showed that piperazine incorporated benzofurans are important class of compounds, wherein piperazine expected to enhance selectivity and biological activity particularly in case of anti-TB activity 5 , 6 . 2-Substituted benzofurans exhibit promising anti-TB activity 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation